Note on the inequalities of J. Kazdan. (1992) - Lee, Will Y.
Abstract : In this note, we prove the Kazdan's inequalities without using what is called the Heisenberg uncertainty principle. Instead we prove it using Garofalo-Lin inequality among other things.